2018
DOI: 10.1096/fj.201801680r
|View full text |Cite
|
Sign up to set email alerts
|

The unraveling of substrate specificity of histone deacetylase 6 domains using acetylome peptide microarrays and peptide libraries

Abstract: Histone deacetylase 6 (HDAC6) is a multidomain cytosolic hydrolase acting mostly on nonhistone protein substrates. Investigations of the substrate specificity of HDAC6 are confounded by the presence of 2 catalytically active deacetylase domains (DD1 and DD2). In this study, acetylome peptide microarrays and peptide libraries were used to map the substrate specificity of DD1 and DD2 of human HDAC6. The results show that DD1 is solely responsible for the deacetylation of substrates harboring the acetyllysine at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(63 citation statements)
references
References 53 publications
3
60
0
Order By: Relevance
“…While several acetylation sites were identified in CTTN under endogenous in vivo conditions, including K124, the site of deacetylation in vivo was unable to be definitively worked out, due to the repetitive nature of the sequence 62 . An in vitro peptide study demonstrated KDAC6 activity using K124 of CTTN as a substrate 91 . While the peptide used in this study is unique, the residues surrounding the acetylated lysine occur several times in the protein.…”
Section: Putative Kdac‐substrate Pairsmentioning
confidence: 95%
See 2 more Smart Citations
“…While several acetylation sites were identified in CTTN under endogenous in vivo conditions, including K124, the site of deacetylation in vivo was unable to be definitively worked out, due to the repetitive nature of the sequence 62 . An in vitro peptide study demonstrated KDAC6 activity using K124 of CTTN as a substrate 91 . While the peptide used in this study is unique, the residues surrounding the acetylated lysine occur several times in the protein.…”
Section: Putative Kdac‐substrate Pairsmentioning
confidence: 95%
“…Acetylation status of G3BP1 K376 has been shown to regulate binding to c‐myc and tau mRNA 64 . This site was identified in the same study as CTTN as a KDAC6 substrate based on deacetylation of a peptide 91 . A few months later, following up on a study that identified a physical interaction between KDAC6 and G3BP1, 116 a separate research group identified acetylation of this same residue from human cells 64 .…”
Section: Putative Kdac‐substrate Pairsmentioning
confidence: 95%
See 1 more Smart Citation
“…Measurements made with cell extracts suggest that CD1 serves as an E3 ubiquitin ligase (Zhang et al, 2014) as well as an RNA helicase DDX3X deacetylase (Saito et al, 2019). However, the only activity that has been confirmed in vitro for a single-domain HDAC6 CD1 construct is as a lysine deacetylase with much narrower substrate specificity than CD2 (Hai & Christianson, 2016;Osko & Christianson, 2019), although the CD1 substrate specificity is reported to be wider in the fulllength enzyme (Kutil et al, 2019). Regardless of the elusive biological functions of HDAC6 CD1, it is important to understand how this catalytic domain accommodates bound inhibitors.…”
Section: Analysis Of Inhibitor Bindingmentioning
confidence: 99%
“…However, the substrate specificity of CD1 is much narrower than that of CD2 owing to amino-acid substitutions in the active site; moreover, the narrow substrate specificity of HDAC6 CD1 from Homo sapiens (human) is even more stringent than that of HDAC6 CD1 from Danio rerio (zebrafish) as measured using single-domain or didomain enzyme constructs (Hai & Christianson, 2016;Osko & Christianson, 2019). Curiously, a recent study of full-length human HDAC6 suggests a wider substrate specificity for CD1 (Kutil et al, 2019), so further studies of both CD1 and CD2 are required in order to fully understand their structure-function relationships.…”
Section: Introductionmentioning
confidence: 99%